Exploring the spirituality and academic resilience among university undergraduate students - Lehihi, Thuto G.; Tsabedze, Wandile F.; Oduaran, Choja A.; Onyencho, Victor Chidi (Frontiers in Education, 2025)
IntroductionSpirituality has been recognized as a potential coping mechanism and source of strength for some students. However, its relationship with academic resilience remains underexplored, especially among South African students. This study aimed to explore the relationship between spirituality and academic resilience among university undergraduate students at a South African university.MethodsA correlational research design was employed, using a web-based questionnaire that combined the Daily Spiritual Experience Scale and the Academic Resilience Scale-30, which included adaptive help seeking, academic reflecting, academic perseverance, negative affect and emotional response and academic reflecting. The Academic Resilience Framework was used as a guiding theoretical framework for this study, supported by theoretical perspectives on spirituality and self-transcendence theory. Data was collected from 420 North-West University undergraduate students, aged between 18 years and older, with stratified random sampling employed (post ad hoc) on the analysis. Data was analyzed using descriptive analysis and inferential analysis that included bivariate correlation, hierarchical multiple regression, and structural equation modeling to test the study’s hypotheses.ResultsThe results of bivariate correlation indicated that spirituality was positively correlated with perseverance, help-seeking, and academic resilience total scores but negatively associated with negative effects. Hierarchical multiple regression analysis results also indicated a positive relationship between spirituality, academic perseverance, academic reflection, adaptive help-seeking, and academic resilience but a negative relationship with negative affect and emotional response. Furthermore, results showed a positive relationship between spirituality and academic resilience in females than in their male counterparts and a negative relationship in participants aged between 18 and 21.ConclusionThe study concluded that there was a positive correlation between spirituality, academic perseverance, academic reflection, and adaptive help-seeking, and academic resilience; however, it was negatively associated with negative effects. It is important for universities and healthcare professionals working with the student population to consider an individual’s spiritual dimension in their programs.